Zika virus disease—knowledge, attitudes and practices among pregnant women—implications for public health practice. (December 2018) - Pooransingh, S.; Parasram, R.; Nandram, N.; Bhagwandeen, B.; Dialsingh, I.
Abstract: Objective: Mosquito-borne diseases continue to pose a threat to Latin America and the Caribbean. Zika virus disease entered the Caribbean in 2013 with increased reporting of cases across the region in 2016, affecting more than 50 countries. This study aimed to ascertain the knowledge of, attitudes and practices towards Zika virus disease among antenatal clinic attenders in Trinidad and Tobago during the 2016 outbreak. Study design: A cross-sectional questionnaire survey was undertaken. Methods: A knowledge attitudes and practices survey was conducted among antenatal clinic attenders at publicly funded primary care health centres. All counties of Trinidad (except St Patrick, Caroni and Victoria) and Tobago were included in the study. Within each county, three health centres were selected at random. At the antenatal clinic of each selected health centre, antenatal clients were selected by randomly selecting their patient file from that day's antenatal clinic patient files. Data collection occurred from September to November 2016. The knowledge, attitudes and practice survey was administered by an interviewer-administered questionnaire. The World Health Organization Knowledge, Attitudes and Practice surveys Zika virus disease and potential complications Resource pack was adapted for use as the data collection tool. All data collected were analysed using SPSS software, version 23. Tests with P -values less than 0.05 were deemed significant. Results: Seventy-four percent (74%) of responders did not think there was a link between sexual transmission and Zika. About 19% stated that abstaining could prevent Zika but only 6.6% actually practiced this. Seventy-six percent knew the risk of microcephaly, and this knowledge of the risk of microcephaly was found to be significantly associated with the number of weeks' gestation. Less than 40% knew the risk of Guillain–Barre syndrome. Doctors at health centres followed by private doctors were the top two trusted information sources for responders. Responders thought that the government could spray insecticide, clean drains, educate community members and clean overgrown vacant lots of land. Conclusion: The government and healthcare workers need to reach specific target groups with accurate messages to minimize the associated morbidity and thereby safeguarding national and global health security. Highlights: Sixty-seven (73.6%) pregnant women did not think that sexual intercourse could lead to Zika. A woman's knowledge of the risk of birth with microcephaly was dependent on the number of weeks pregnant ( P -value = 0.002). Nineteen percent stated that abstaining could prevent Zika but 6.6% actually practiced this.